Diagnostic technology for inflammatory changes in the skeleton with ankylosing spondylitis according to magnetic resonance imaging - Sh. Erdes; A. V. Smirnov (Научно-практическая ревматология)
The paper describes diagnostic technology for inflammatory changes in the spine and sacroiliac joints using magnetic resonance imaging if axial spondyloarthritis is present or during a followup.